Hubungan Penguasaan Kosakata dan Minat Menulis Dengan Kemampuan Menulis Surat Resmi Pada Siswa Kelas VIII SMP Negeri 3 Jati Agung Lampung Selatan - Sari, Resti Riyana (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The problem that raised in this research is the relationship writer of vocabulary and effective sentence mastery with formal letter writing ability. This research was motivated by the fact in field that the ability of letter writing and effective and the relationship between mastery of vocabulary need to describe the relationship between mastery of vocabulary and effective sentence mastery with formal letter writing ability at seven SMPN 3 Jati Agung.To reach the purpose of the research above, the researcher use correlational methos, it means that the data collected after all the even happen. The techniques to collect the data are analytical conditional test, statistical analyze, and research hypothesis test. The research indicates findings, those: (1) There are positive and significant relationship between mastery of vocabulary and the ability to write a formal letter, whith a correlation coefficient ry1 = 0.782 and regression equation Ỹ = 45,097 + 0.389X1; (2) There is positive and significant relationship between mastery of effective sentence with the ability to write formal letter, with coefficient ry2 = 0.775 and regression equation Ỹ = 49,583 + 0.347X2; and (3) There is relationship between both mastery of vocabulary and mastery of effective sentence with a correlation coefficient ry1,2 = 0.786 and regression equation Ỹ = 18,831 + 0.391 X1 + 0.349 X2. Based on these research data, it can be conclude that mastery of vocabulary and mastery of effective sentence are two main factors affecting the ability to write a formal letter.